Epidemiology of multidrug-resistant Klebsiella pneumoniae infection in clinical setting in South-Eastern Asia: a systematic review and meta-analysis - Salawudeen, Adamu; Raji, Yakubu Egigogo; Jibo, Garba Gidandawa; Mohd Desa, Mohd Nasir; Neoh, Hui-min; Masri, Siti Norbaya; Di Gregorio, Sabrina; Tengku Jamaluddin, Tengku Zetty Maztura (Springer Science and Business Media, 2023)
The rising prevalence of multidrug-resistant (MDR) and extended-spectrum beta lactamase-resistant (ESBL) Klebsiella pneumoniae (K. pneumoniae) is an important global public health challenge. This threat is even more pertinent in clinical settings. Morbidity and mortality associated with this condition are alarming particularly in the developing regions of the world. A comprehensive evaluation of the epidemiology of this phenomenon will assist towards the global effort of reducing its burden. So, this systematic review and meta-analysis was conducted to evaluate the epidemiology of MDR K. pneumoniae in South-Eastern Asia (SEA). The study was done under the PRISMA guidelines and was preceded by the development of a priori protocol. The protocol was then registered in PROSPERO—the public registry for systematic reviews. Seven important outcomes which include the assessment of the overall MDR K. pneumoniae prevalence were designed to be evaluated. A literature search was carried out in five selected electronic databases and 4389 were screened. Of these articles, 21 studies that met the eligibility criteria were included in the review. Relevant data were extracted from the included studies. By conducting a quality effect meta-analysis, the pooled prevalence for MDR and ESBL K. pneumoniae in SEA was estimated at 55% (CI 9–96) and 27% (CI 32–100) respectively. The review also identified ESBL genes types of allodemic situations occurring mostly in respiratory tract infections. The high prevalence of MDR and ESBL K. pneumoniae in this subregion is highly significant and of both public health and clinical relevance. Overall, the findings of this review will assist in the effective prevention and control of this threat in SEA.